THE INFLUENCE OF AFFILIATE MARKETING AND PROMOTIONS ON THE PRODUCT PURCHASE DECISION ON TIKTOK SOCIAL COMMERCE - Apriyanto, Bagas; Affar, Muhammad (Kinerja, 2025)
This study aims to analyze the influence of affiliate marketing and promotion on product purchase decisions on the TikTok social commerce platform. The method used is a quantitative approach with multiple linear regression analysis and classical assumption tests. The population in this study is TikTok social commerce users in Jatiasih District.This study uses questionnaires as data collection materials with a sample of 130 respondents, this study uses the SPSS program in conducting data processing. The test results showed the data met classical assumptions and significant regression models. Affiliate Marketing (β = 0.385) and Promotion (β = 0.311) have a positive and significant effect on Purchase Decisions (Sig. < 0.05). An R² value of 0.498 indicates that both variables explain 49.8% of the variation in purchasing decisions, and the remaining 50.2% is influenced by other factors outside the model. The F test also showed significant simultaneous influence (F = 62.943; Sig. = 0.000). Thus, it can be concluded that Affiliate Marketing and Promotion partially or simultaneously have a significant effect on product purchase decisions on TikTok social commerce. This model can be used as a basis for decision-making digital marketing strategies on social commerce platforms.